Stifling of Customary People Political Voice of Recognition in Political Economy Perspective (Case Study on Mapur Tribe Lom Bangka Belitung) - Zulkarnain, Iskandar; Soetarto, Endriatmo; Sunito, Satyawan; Adiwibowo, Soeryo (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2018)
Symptoms of political neglection along with changes in capitalist-oriented economic development policies have become a major challenge for recognition of indigenous people in Indonesia. The experience of the Mapur Lom tribe marks the phase of detachment of an entity from its agrarian tradition. This study aims to identify the future critical point of Lom people due to the absence of recognition from the government which more prioritizes the practices of power domination and penetration of capital. The case study was used to oversee the socio-economic relations between tin and oil palm as well as the dynamics of actors contestation who were legitimized by the post-New Order bureaucracy. Data collection uses interviews, observation, document studies, and focused discussions. The results of the research show that the mechanism of stifling the political voice of Lom people's recognition takes place through two phases, namely silencing from within by the apparatus at the hamlet level by hijacking the autonomy discourse of customary forests. The second phase, preclusion of political voices from outside through a continuous changing of regulations, policies that tend to favor the oil palm plantation corporations, capital intervention accompanied with land grab and violence. Working with Marxian perspective elaboration and critical perspective see that failure of state and bureaucracy at the regional level related to political economy of recognition are the result of perpetuating power domination based on concentration of regulation, policy, legitimacy, and capital along with collusion with corporations against individuals, groups and nature.